Bioremediation and phytoremediation of diesel fuel contaminated soil using organic wastes / Arezoo Dadras Nia - Dadrasnia, Arezoo (2013)
Contamination of soil by organic compounds, especially hydrocarbon, is prevalent in industrialized and oil producing countries of the world. About 1.7 to 8.8 million metric tons of oil is released into the water and soils every year. This may pose a great threat to the environment and human being at large. This study evaluated the efficiency of organic wastes (biowastes) as supplementations for remediation of diesel fuel contaminated soil. Three organic wastes [tea leaf (TL), Soybean cake (SC) and Potato skin (PS)] and two economically viable plants (Dracaena reflexa and Podocarpus polystachyus) were utilized to evaluate the biodegradation of diesel fuel in soil contaminated with different concentrations of oil. For biodegradation studies, soils were treated with 20%, 15%, 10% and 5% (w/w) diesel fuel and amended with 10% and 5% TL, SC and PS. Completely randomized design was used for a period of 126 days under laboratory condition. At the end of 126 days, soil polluted with 20% diesel oil and amended with 5% TL recorded the lowest percentage of oil degradation (14.5%) and diesel utilizing bacteria at 30×105 colony-forming units (CFU) per gram of soil. The highest rate of biodegradation (95%) was recorded in soil polluted with 5% diesel oil and amended with 10% SC with the count of diesel utilizing bacteria at 210×105 CFU/g. First order kinetic showed that soil amended with SC had the highest rate of oil degradation and illustrates the least half-life for all the diesel fuel concentrations. Bioremediation of diesel fuel contaminated soil with biomass amendments was monitored for a period of one year under natural condition. Result indicates complete biodegradation of C8 to C16 and remarkable biodegradation of C16 to C22 hydrocarbon fractions in contaminated soil amended with SC. In phytoremediation study, contamination of soil with 2.5% and 1% diesel fuel and amended with 5% of the three different organic residues was monitored for a period of 270 days under laboratory and natural conditions. About 98.8%, 90.3% and 19% oil loss was recorded in soil amended with SC, polluted with 1%, 2.5% and 5% diesel oil planted with D. reflexa, respectively. However, diesel contaminated soil with Dracaena but without organic wastes recorded 62%, 52.4% and 8.5% for 1%, 2.5% and 5% contamination, respectively under laboratory condition. Also 91%, 84% and 13.8% oil loss was recorded in soil amended with SC, polluted with 1%, 2.5% and 5% diesel oil with P. polystachyus, respectively. The remediation process was influenced by oil concentration and organic biomass added. However, D. reflexa and P. polystachyus root did not accumulate hydrocarbons from the soil, thus indicating that the mechanism of the oil degradation was via phytovolatilization or rhizodegradation. Phytoremediation of cocontamination of soil with heavy metals (80 ppm Zn and 60 ppm Pb) and 2.5% diesel fuel was amended with 5% organic waste was studied for a period of 180 days. Significant bioaccumulation of Pb and Zn in the root and stem of Dracaena plant was observed. At the end of 180 days, 16.53 mg/kg and 12.2 mg/kg of Zn accumulation in root and stem while 16.7 mg/kg and 9.8 mg/kg of Pb in root and stem of D. reflexa was recorded, respectively. However, 11.8 mg/kg and 9.8 mg/kg bioaccumulation of Zn and Pb was observed in root of P. polystachyus. Potential of five diesel utilizing bacterial (DUB) isolates (Stenotrophomonas acidaminiphila, Bacillus lichenifomis, Brevibacillus parabrevis, Ochrobactrum tritici, Pesedomonas citronellolis) from oil-contaminated soil to degrade diesel fuel was studied in broth culture for 35 days at 320C. At the end of the incubation period higher percentage degradation was recorded for Bacillus lichenifomis (45.8%). In conclusion, the results of these studies illustrated the potential of SC and the two plants (D. reflexa and P. polystachyus) as a good option for enhanced remediation of hydrocarbon-contaminated soil.